Effect of air gap on polyethersulfone / polyvinyl alcohol – zno hollow fiber membrane for fouling mitigation / Zulfida Mohamad Hafis Mohd Shafie - Mohd Shafie, Zulfida Mohamad Hafis (2017)
Membrane separation process for water application has always been challenges by its tendency to foul. Fouling, especially at industrial scale is a ubiquitous, cost deterring, and performance degrading phenomenon which needs to be nullified. Periodic cleaning, while being effective to mitigate fouling consequences to some extent, impose a threat to the membrane’s mechanical and chemical integrity. It has also been found to be ineffective in battling biofilm formation; a side product of biofouling. Hence, in the current work, new dope formulation was synthesized as an effort to fabricate an antifouling hollow fiber (HF) membrane using PES/PVA blend. The membrane was tested against humic acid as model foulant. The blend was mediated by LiCl as membrane pore former and to improve the solubility of PVA through the formation of transition state with N,N-dimethylacetamide (DMAc) solvent system. Using the formulation, HF membranes were spun (dry jet-wet spinning) at different air gap distances to study the effect under gravitational stretching. Four different air gap distances (5, 10, 15 & 20 cm, corresponds to sample A.1, A.2, A.3 & A.4 respectively) were investigated and characterized through various means. Peculiar morphology and topography was found through the use of this new formulation, on top of being idiosyncratically affected by the air gap/gravitational stretching. After 30 minutes of hydraulic compaction and 1 hour of deionized water permeation, maximum water flux was noted at 42.32 ± 0.12 kg/m2.h for sample A.3 with air gap distance of 15 cm. Similar trend was noted after another 1 hour of foulant permeation, with maximum humic acid flux was found at 42.86 ± 0.09 kg/m2.h for the same membrane sample A.3. Nevertheless, rejection was found to be highest for sample A.1, spun at 5 xviii cm air gap distance with 94.63 ± 2.13 % humic acid rejection. After considering the permeation-rejection relationship and other factors such as surface roughness, mechanical strength & hydrophilicity, 10 cm was noted to be the suitable air gap distance for the fabricated PES/PVA hollow fiber membrane and its future derivative with similar formulation. Subsequent study was done in characterizing and comparing the performance of the PES-PVA membrane (sample B.3) with neat PES (sample B.1), PES blended with zinc oxide (ZnO) nanoparticle (sample B.2), and PES blended with PVA-ZnO (sample B.4). The addition of PVA in sample B.3 & B.4 suppressed the macrovoid formation and improved the antifouling properties of the membrane with the lowest recorded relative humic acid flux (HAF) of not less than 0.95, as compared to HF membranes without PVA (sample B.1 & B.2) which has relative HAF of around 0.75 – 0.85 by the end of the 2 hours flux duration. Nevertheless, incorporation of PVA reduced the water flux of sample B.3 down to 33.04 ± 0.09 kg/m2.h as compared to neat PES membrane (sample B.1) at 91.42 ± 0.05 kg/m2.h. ZnO on the other hand was able to improve the water flux of sample B.2 to 123.20 ± 0.14 kg/m2.h as compared to the neat membrane, but made the HF much more susceptible to fouling. PVA-ZnO incorporation in sample B.4 didn’t improved the flux performance, but improved the humic acid rejection from 91.27 ± 2.28 % in neat PES (sample B.1) to 96.03 ± 1.07 %. With further optimization of the formulation (especially PVA/ZnO ratio), it is expected that the fabricated membranes would have improved anti-fouling properties and rejection without severing its flux performance